2020
DOI: 10.1088/1361-6528/abbddc
|View full text |Cite
|
Sign up to set email alerts
|

Friction force reduction for electrical terminals using graphene coating

Abstract: Multi-layer graphene, serving as a conductive solid lubricant, is coated on the metal surface of electrical terminals. This graphene layer reduces the wear and the friction between two sliding metal surfaces while maintaining the same level of electrical conduction when a pair of terminals engage. The friction between the metal surfaces was tested under dry sliding in a cyclical insertion process with and without the graphene coating. Comprehensive characterizations were performed on the terminals to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Fascinating lubricant properties are attributed to graphene by Penkov et al [15], who collected and revised in his paper many results from previous tribological investigations at the nanoscale and macroscale on a number of substrates. Zhang et al [16] reported that the use of multi-layer graphene coating can effectively reduce the wearing-out of tiny electrical connectors and protect them from tribo-oxidation damage, without affecting the electrical conduction through the pair. Lin et al [17] explored the synergistic effect of TiN-Ag coating and MLG-rich grease to improve the friction, wear, and conduction of copper connectors.…”
Section: Introductionmentioning
confidence: 99%
“…Fascinating lubricant properties are attributed to graphene by Penkov et al [15], who collected and revised in his paper many results from previous tribological investigations at the nanoscale and macroscale on a number of substrates. Zhang et al [16] reported that the use of multi-layer graphene coating can effectively reduce the wearing-out of tiny electrical connectors and protect them from tribo-oxidation damage, without affecting the electrical conduction through the pair. Lin et al [17] explored the synergistic effect of TiN-Ag coating and MLG-rich grease to improve the friction, wear, and conduction of copper connectors.…”
Section: Introductionmentioning
confidence: 99%